Creating and sustaining healthy work environment for professional advancement in health care institutions: a case study of nursing students’ clinical posting in Abia State - E., Enwereji Ezinne; C., Ezeama Martina; O., Enwereji Kelechi (International Journal of Research in Medical Sciences, 2017)
Background: The need for nursing students to care and support patients especially those living positively with HIV and AIDS as well as those with terminal diseases should not be underestimated. By training, nursing students are expected to interact cordially with patients and other health care professionals but most times, the reverse is the case. Inter-professional and interpersonal education prepare nursing students on clinical posting to provide quality health care services to all patients irrespective of their ages and health conditions. Therefore, creating healthy work environment by encouraging team work, integrating treatment and prevention services to promote good health is imperative in ensuring patients’ safety, and enhanced inter-professional relationship. Methods: A two-day pre-clinical seminar which centered on professionalism, teamwork, interpersonal and inter-professional relationships, as well as effective communication to guarantee healthy work environments was carried out. The pre-clinical seminar was also used to prepare 186 nursing students on their expected roles during the twelve weeks’ clinical posting in health institutions. At the end of the students’ posting, two days post-clinical seminar aimed to harness students’ experiences, views and performances, as well as the teachers’ observations during the clinical posting was conducted. Thereafter, all comments on performances, observations, experiences and other remarks from the teachers and students were grouped together and analyzed qualitatively and quantitatively. Results: A good proportion of the students 142 (76.3%) established good interpersonal relationship with the patients who are HIV positive while 135 (72.6%) had effective inter-professional interaction with health care workers. Also 135 (72.6%) had good team work relationship with other health care professionals. There were better health care services to clients as evidenced by 95 (51.1%) of students who shared case managements with the health care workers and 122 (65.6%) of the students who used mobilization and advocacy to identify pressing challenges like inter-professional conflicts, poor uptake of messages about treatment and referrals as well as malnutrition among children. A respectable number of the students, 144 (77.4%) collaborated with colleagues to provide nutrition to malnourished children to improve their nutritional status, while 75 (40.3%) assisted in resolving some inter-professional conflicts. Conclusions: Students’ initiatives in management of cases, inter-professional and interpersonal learning experiences during clinical postings increased students’ understanding of teamwork and professionalism as well as promoted friendlier environments that guaranteed better health care services to patients.